2011
DOI: 10.4081/ijas.2011.e26
|View full text |Cite
|
Sign up to set email alerts
|

Use of yeast cell walls andYucca schidigeraextract in layer hens’ diets

Abstract: This research was conducted to determine the impact of diet supplementation with yeast cell walls (YCW) and Yucca schidigera extract (YE) on performance, egg weight, specific gravity, body weight, and intestinal tissue histology in layer hens. White, 48-week-old, Hyline hybrid hens (n=320) were divided into four main groups, each comprising eight groups of 10 hens: (1) control, (2) 500 mg/kg YCW added, (3) 500 mg/kg YE added and (4) 250 mg/kg YE plus 2500 mg/kg YCW added. While the egg production and feed inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
2
11
1
1
Order By: Relevance
“…It is known that the phenolic concentrations in the whole YS plant are much lower than its bark (Oleszek et al, ). Hence, the even higher YSE dosage may continue to exhibit positive antioxidant functions to broilers as indicated by Gurbuz, Balevi, Kurtoglu, and Oznurlu (). Our results suggest that there is no need to increase the YSE level to broilers beyond the optimum, which we here found to be 100–200 mg/kg.…”
Section: Discussionmentioning
confidence: 88%
“…It is known that the phenolic concentrations in the whole YS plant are much lower than its bark (Oleszek et al, ). Hence, the even higher YSE dosage may continue to exhibit positive antioxidant functions to broilers as indicated by Gurbuz, Balevi, Kurtoglu, and Oznurlu (). Our results suggest that there is no need to increase the YSE level to broilers beyond the optimum, which we here found to be 100–200 mg/kg.…”
Section: Discussionmentioning
confidence: 88%
“…The present study revealed no significant effects of feeding saponin rich SSP on the intestinal histomorphometry of broiler chicken. However, in contrast to these results greater villus height of jejunum and ileum was observed in layer chicken fed dietary Yucca schidigera extract (Gurbuz et al, ) and increase in villus height and crypt depth of duodenum and jejunum of Muscovy ducks was observed by feeding saponin rich alfalfa meal (Jiang et al, ). The variation in the results of saponin effects on intestinal mucosa in different studies may be due to the interaction of ingested saponins with many potential ligands in the intestine such as bile salts, dietary cholesterol, membrane sterols of the mucosal cells and nutrients or antinutrients present in feed, all of which may reduce or enhance their effectiveness.…”
Section: Discussionmentioning
confidence: 89%
“…The saponins from Yucca schidigera were found to have differential effects on gut microbes, whereby, the faecal E. coli growth in layer chicken is significantly inhibited with no effect on the Lactobacillus count (Wang & Kim, 2012). The improved gut architecture has been observed in layer chicken fed dietary Yucca schidigera extract (Gurbuz, Balevi, Kurtoglu, & Oznurlu, 2011) and in Muscovy ducks fed saponin rich alfalfa meal (Jiang et al, 2012). Thus, the addition of medicinal plant extracts to animal diets is not a new idea, and both Yucca and Quillaja saponins are commercially available products that have been used as feed additives.…”
mentioning
confidence: 98%
“…Enhances bird's growth and production, improves the metabolic efficacy, decreases the ammonia level, and increases the feed utilization in production of broilers (Sahoo et al, 2015). Significant increase in weight was recorded in the Yucca treated groups when compared to yeast cell walls and Yucca schidigera extraction in the diet of chickens (Gurbuz et al, 2011). The 38% reduction in ammonia was observed by using commercial preparation of Yucca schidigera (Karamanlis et al, 2008).…”
Section: Introductionmentioning
confidence: 96%